An Investigation into Indonesian EFL Learners’ First and Second Language Identity Development - Sugianti, Lilik (Master Program in Linguistics, Diponegoro University, 2024)
Some researchers have challenged the framework by proposing a poststructuralist model that captured the L2 complication learning and made outcomes of learning difficult to predict. They attempted to maintain that linguistic communities may have diverse and even contradictory opinions. This study investigated the case of two students who joined a student exchange to the UK and the US regarding the impact of learning their L1and L2 experiences and changes in social context on the construction of their L1 and L2 identities. It found that as English learners as a Foreign Language (EFL), the identity advancement of these two students was in line with poststructuralist theory. Their identity considered fluid, dynamic, and contradictory. The two students negotiated and renegotiated their identities in various social contexts in Indonesia-UK and Indonesia-US, and they were finally accepted into the L2 academic community. This study also analyzed two Indonesian students' experiences in language learning and identity. The paper also highlighted that conflict could be an element of students’ identity construction and encouraged them to be persistent and self-resilient while being able to navigate through negative encounters that take place amid the proses of second language acquisition.